1968
DOI: 10.1021/j100848a002
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of the aqueous nitrate system. I. Excitation in the 300-m.mu. band

Abstract: Nitrate solutions have been photolyzed in the first weak band at 300 mp using the filtered output of a 450-W high-pressure mercury lamp. In neutral solution, nitrite formation is initially nonlinear with time, falling off to a low constant rate. This behavior has been investigated as a function of nitrate concentration, nitrite buildup, and addition of nitrite prior to photolysis, The results are quantitatively consistent with process A NO3--% NO2-+ 0 0 + Nos--% 0 2 + Not-and allow evaluation of kz/kl as -2 X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
2
1

Year Published

1969
1969
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 2 publications
(2 reference statements)
3
76
2
1
Order By: Relevance
“…Kudo et al [18] irradiated 1M NaNO 3 and 1M HNO 3 , respectively, in experiments similar to ours and observed the formation of nitrite with a rate of 0.3 µmol/h in both cases. An increasing rate of formation of nitrite with increasing pH in the range of 5 to 8 was reported by Daniels [5], Wagner [6], Warneck [7], and Shuali [31]. Photoreduction of nitrate to nitrite has also been applied for the quantitative analysis of nitrate [32,33], with an increased reduction efficiency at increased pH.…”
Section: Photoinduced Reduction Of Nitratementioning
confidence: 83%
See 2 more Smart Citations
“…Kudo et al [18] irradiated 1M NaNO 3 and 1M HNO 3 , respectively, in experiments similar to ours and observed the formation of nitrite with a rate of 0.3 µmol/h in both cases. An increasing rate of formation of nitrite with increasing pH in the range of 5 to 8 was reported by Daniels [5], Wagner [6], Warneck [7], and Shuali [31]. Photoreduction of nitrate to nitrite has also been applied for the quantitative analysis of nitrate [32,33], with an increased reduction efficiency at increased pH.…”
Section: Photoinduced Reduction Of Nitratementioning
confidence: 83%
“…Further investigations [3][4][5][6]30,31] yielded inconsistent results regarding a nitrate/nitrite equilibrium [3,4] and regarding the product distribution which besides nitrite has been reported to include oxygen atoms [3,5], molecular oxygen [6,31], hydrogen peroxide [6], hydroxyl radicals [31], peroxynitrate [6], and pernitrite [31]. In Warneck's more recent investigations [7] two pathways of nitrate photodecomposition are suggested, one giving nitrite and oxygen atoms and one giving nitric oxide and oxygen radical anions.…”
Section: Photoinduced Reduction Of Nitratementioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we introduce two broadband sunlight actinometers that are based on the photolysis of nitrate (29)(30)(31)(32)(33)(34) and nitrite (32,(35)(36)(37). The primary reactive intermediate of nitrate and nitrite photolysis, the hydroxyl radical, reacts with benzoic acid leading to the formation of monohydroxybenzoic acids (38), including SA or pHBA (39).…”
Section: Introductionmentioning
confidence: 99%
“…The NO~ oxidizer is also formed at much blander conditions (about 10-50 Torr and room temperature) from NO or NzO3 and oxygen (Guillory andJohnston, 1963, 1965). This transient may, in turn, be expected to yield highly oxidizing OH" or O ~ radicals during its decomposition in solution (Martin et al, 1964) which, in turn, could react with NO~ yielding again NO~ (Daniels et al, 1968;Daniels and Wigg, 1969). It has also been shown that radiolysis of nitrates in aqueous solution yields those radicals (Hyder, 1965;Daniels, 1966) whereby subsequent formation of NO 2 may be expected in those aqueous systems.…”
Section: Some Reactions Which Involve Nitrogen-oxides and The Correspmentioning
confidence: 99%